A Comprehensive Study on Gamma Rays and Fast Neutron Sensing Properties of GAGOC and CMO Scintillators for Shielding Radiation Applications - Shams A. M. Issa; M. I. Sayyed; M. H. M. Zaid; K. A. Matori (Journal of Spectroscopy)
The WinXCom program has been used to calculate the mass attenuation coefficients (μm), effective atomic numbers (Zeff), effective electron densities (Nel), half-value layer (HVL), and mean free path (MFP) in the energy range 1 keV–100 GeV for Gd3Al2Ga3O12Ce (GAGOC) and CaMoO4 (CMO) scintillator materials. The geometrical progression (G-P) method has been used to compute the exposure buildup factors (EBF) and gamma ray energy absorption (EABF) in the photon energy range 0.015–15 MeV and up to a 40 penetration depth (mfp). In addition, the values of the removal cross section for a fast neutron ∑R have been calculated. The computed data observes that GAGOC showed excellent γ-rays and neutrons sensing a response in the broad energy range. This work could be useful for nuclear radiation sensors, detectors, nuclear medicine applications (medical imaging and mammography), nuclear engineering, and space technology.